Lifestyle entrepreneurship innovation and self‐efficacy: Exploring the direct and indirect effects of marshaling - Dias, Á. (2022)
Lifestyle entrepreneurs play a key role in the destination sustainable development by providing more authentic and innovative experiences. However, the determinants of the innovation generated by these entrepreneurs are not fully understood. This study explores the key factors influencing Innovation and entrepreneurial Self-Efficacy (ESE) in Lifestyle entrepreneurs. Survey data allowed to identify the effect of marshaling, place familiarity, and communication on innovation and ESE. Findings reveal several direct and indirect relationships between these variables. The results indicate that marshaling has a significantly positive and direct effect on both ESE and communication. Communication has a direct and positive relationship with innovation. Place familiarity perception has a significantly positive and direct relation to communication and innovation on ESE. It was also found an indirect link between marshaling and innovation via communication as a mediator.